Temporibus Inserviendum in termination disputes, the regular courts for corporate officers and the national labor relations commission for non-corporate officers - Sobreviñas, Francis V. (Journal of the Philippine Association on Voluntary Arbitration)
Examines the issue of jurisdiction over termination disputes involving high ranking officers of a corporation, partnership or association. The cases provide guidelines to observe in determining whether the controversy is an intra-corporate dispute or one that arises from employer-employee relationship.